Building structures : understanding the basics - Millais, Malcolm (Routledge, Taylor & Francis Group, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface to the Third Edition -- Introduction -- 0.1 Prehistoric design -- 0.2 Traditional design -- 0.3 The effect of civilisation -- 0.4 The search for structural understanding -- 0.5 The modern approach to structural design -- 0.6 The conceptual understanding of structural behaviour -- References - Introduction -- Chapter 1 Loads and load